Optimization of oil palm-based cellulose and hydroxyapatite-carbon composite electrode for trace Pb(II) ions detection in aqueous system - Ajab, H. (North Carolina State University, 2020)
An electroanalytical technique was devised using oil palm-based cellulose and hydroxyapatite as modifiers to carbon electrodes for Pb(II) ions detection in an aqueous system. The cyclic voltammetry scan suggested increased active binding sites and faster electron transfer with quasireversible redox peaks with a larger anodic current peak and smaller oxidation potential values. The optimal conditions were attained using 10 modifier at pH 2 in 0.1 M HCl,-1.2 V deposition potential, 270 s deposition time, 25 Hz frequency, 0.020 V amplitude, rotation speed of 700 rpm, and the step potential of 0.005 V. The square wave anodic stripping voltammetry established at optimum level exhibited excellent selectivity and stability from 10 ppb to 100 ppb for Pb(II) ions detection. Sharp anodic peaks were observed at-0.48 V for Pb(II) ions with the detection limit of 0.095 ± 0.32 ppb and limit of quantitation of 0.32 ± 0.32 ppb. © 2020 North Carolina State University.